The relationship between social life and emotions. Adam Ferguson and sociology - Bevilacqua, Emiliano (Frontiers in Sociology, 2023)
Adam Ferguson has a leading position among those who have developed a sociological interpretation of modernity that dismiss metaphysics without following the echoes of rationalism. Ferguson outlines a vision of social life that correlates the analysis of individual behavior to the study of social context and institutions. Consistently with this approach, the Scottish scholar emphasizes the multidimensionality of human beings without forgetting the non-rational features of social behavior. This essay aims to discuss Ferguson's thought with a special attention to the importance of the emotions in social life, so as to enhance the contribution of classical sociology to the analysis of the emotionality. Ferguson, in fact, argues that emotions have a leading role in shaping the behaviors and values of individuals. Developed in the context of Scottish Enlightenment, Ferguson's sociology shows how the study of modern society can be reconciled with a reasonable as well as emotional approach to social life.